Peak running speed can be used to monitor neuromuscular fatigue from a standardized running test in team sport athletes - Garrett, J.; Akyildiz, Z.; Leduc, C.; van den Hoek, D.; Clemente, F. M.; Ardigò, L. P. (Research in Sports Medicine, 2023)
This study compared the sensitivity of peak running speed (PRS) measured during a submaximal run test (SRT) with a countermovement jump (CMJ) test to provide an alternate method of measuring neuromuscular fatigue (NMF). The study involved 20 semi-professional academy soccer players who performed a SRT and CMJ test, 24-hours pre-match, 24-, 48-, 72- and 96-hours post-match. Moderate decreases (effect-size (ES) ± 90% confidence intervals) were observed 24-hours post-match for CMJH; ES -0.70 ± 0.19, CMJPV; ES -0.92 ± 0.27 and PRS; ES -0.58 ± 0.11 with small decreases in CMJH; ES -0.36 ± 0.13 and PRS; ES -0.27 ± 0.23 still evident 48-hours post-match before returning to baseline 72-hours post-match. The results confirm PRS as an inexpensive alternate method of measuring NMF which, allows instantaneous real-time feedback on NMF. This can allow changes to be made immediately on-field within the post-match recovery phase without the need for further analysis or equipment.